The work of inclusion an ethnography of grace, sin, and intellectual disabilities - Cuddeback-Gedeon, Lorraine (T&t clark studies in social ethics, ethnography and theologies, 2022)
Using ethnographic research, The Work of Inclusion brings the standpoints of people with intellectual disabilities to the forefront of the theological conversation around disability, inclusion, grace, and sin. In a world shaped by interdependency, developing a theological attunement to intellectual disability helps us to understand that human agency is both enabled by and limited by dependency relationships. Only by recognizing the kinds of complex layers of agency seen in this ethnographic study can Christian ethics more broadly address the place of hope, grace, and resistance against structures of sin and injustice"--